Hemichannel composition and electrical synaptic transmission: molecular diversity and its implications for electrical rectification - Palacios-Prado, Nicolás; Huetteroth, Wolf; Pereda, Alberto E. (Frontiers in Cellular Neuroscience, 2014)
Unapposed hemichannels formed by oligomerized hexamers of gap junction proteins are now known to be involved in various cellular processes under both physiological and pathological conditions. On the other hand, less is known regarding how disparities in the molecular composition of hemichannels impact electrical synaptic transmission between neurons when they form intercellular heterotypic gap junctions. Here we review data indicating that molecular differences between apposed hemichannels at electrical synapses are generally associated with rectification of electrical transmission. Furthermore, this association has been observed at both innexin and connexin based electrical synapses. We discuss the possible molecular mechanisms underlying electrical rectification, as well as the potential contribution of intracellular soluble factors to this phenomenon. Thus, asymmetries in molecular composition and sensitivity to cellular factors of each contributing hemichannel can profoundly influence the transmission of electrical signals, endowing electrical synapses with more complex functional properties.